Molecular Basis of LH Action on Breast Cancer Cell Migration and Invasion via Kinase and Scaffold Proteins - Mondaca, Joselina Magali; Uzair, Ivonne Denise; Castro Guijarro, Ana Carla; Flamini, Marina Inés; Sanchez, Angel Matias (Frontiers in Cell and Developmental Biology, 2021)
Breast cancer (BC) is a major public health problem affecting women worldwide. Approximately 80% of diagnosed cases are hormone-dependent breast cancers. These hormones are known to stimulate tumor development and progression. In this setting, tentative evidence suggests that luteinizing hormone (LH) may also play a role in tumors. In BC cells that express functional LH receptors (LHR), this hormone regulates cell migration and invasion by controlling several kinases that activate actin cytoskeletal proteins. In this article, we show that LH induces phosphorylation of paxillin and its translocation toward the plasmatic membrane, where focal adhesion complexes are assembled. This process is triggered via a rapid extra-gonadal LHR signaling to Src/FAK/paxillin, which results in the phosphorylation/activation of the nucleation promoter factors cortactin and N-WASP. As a consequence, Arp2/3 complexes induce actin polymerization, essential to promote cell adhesion, migration and invasion, thus enhancing metastatic spread of tumoral cells. Our findings provide relevant information about how gonadotrophins exert their action in BC. This information helps to understand the extragonadal effects of LH on BC metastasis. It may provide new perspectives for therapeutic treatment, especially for women with high serum levels of gonadotrophins.